Writing Sámi Memory and Trauma into Swedish History: Linnea Axelsson’s Ædnan. Epos (2018) and Elin Anna Labba’s Herrarna Satte Oss Hit. Om Tvångsförflyttningar i Sverige (2020) - Broomans, Petra (Scandinavistica Vilnensis, 2023)
After Sweden and Norway signed the reindeer grazing convention agreement in 1919, reindeer-herding Sámi families selected by the Swedish authorities were forced to migrate from the Karesuando area in Norway to more southern regions within the reindeer husbandry area in Sweden. These relocations at the beginning of the twentieth century are the source of memory and trauma in both Linnea Axelsson’s Ædnan. Epos (2018; Ædnan. An Epic) and Elin Anna Labba’s Herrarna satte oss hit. Om tvångsförflyttningar i Sverige (2020; The Masters Put Us Here. On Forced Relocations in Sweden). Furthermore, the two works contain paratextual fragments that express the desire to make the silenced past of the Sámi audible in Swedish history. Each text transmits memories and traumas from different genre perspectives: those of poetry and partly autobiographical non-fiction. The texts reveal processes of colonization and oppression within national borders, with scientific racism as an underlying ideology.In this contribution also a methodological issue will be discussed. How should we study texts that deal with writing about trauma and memory of a minority people such as the Sámi? An indigenous methodology, as presented by authors such as Jelena Porsanger in “An Essay about Indigenous Methodology” (2004), should be an important guide, as it concerns a respectful approach to the study of indigenous minority people.“
Keywords: Sámi literature; Swedish history; Forced Migration; Memory; Trauma; Indigenous methodology; Paratexts; Cultural Transfer; Linnea Axelsson; Elin Anna Labba